Filosofi Informasi Dalam Pemberdayaan Layanan Perpustakaan - Alam, Umar Falahul (STAIN Ponorogo, 2014)
Abstract:Â The existence of the library indicates information services.Â TheÂ serviceÂ showsÂ twoÂ interrelatedÂ variables: theÂ providerÂ onÂ theÂ oneÂ handÂ andÂ consumersÂ onÂ theÂ other. Because of relation between service provider and customer satisfaction, then the service should beÂ increasedÂ from time to time. Library services also needs to be improved. Increased libraryÂ services mustÂ beÂ appropriatedÂ byÂ itâsÂ responsibilityÂ to supportÂ education,Â teaching,Â researchÂ andÂ community service. There is no doubt, that the library plays an important role inÂ theÂ processÂ ofÂ educationÂ andÂ teaching. TheÂ frstÂ library becomesÂ anÂ intermediaryÂ betweenÂ theÂ usersÂ andÂ their information needs. Second, the library can be an information providerÂ onÂ oneÂ sideÂ andÂ can beÂ consultedÂ forÂ the usersÂ in their academic activities. Third, the library can be a teacher who teaches the users the skills and strategies in managing, utilizing, andÂ creatingÂ information. TheÂ role ofÂ theÂ library likes this, is named empowerment of library services